O IMPACTO DA SARS-COV-2 NA ACTIVIDADE CIRÚRGICA VASCULAR NUM HOSPITAL TERCIÁRIO
Introduction/Objectives: The Corona Virus Disease of 2019 (COVID-19) has taken a major toll on the public health system, with restrictions in all clinical activity, from consultations and exams to number and type of surgeries. Patients apprehension to resort to medical aid and hospitals leads to late admissions and, in our perception, more severe presentations of the underlying pathology, namely, in Chronic limb threatening ischemia (CLTI). Need for testing prior to non-emergent surgery causes larger delays in the referral of patients, and this, added to the reduction of surgical times and ICU availability, potentially results in worse outcomes. The aim of this study was to objectively evaluate the type pathology that was treated during the emergency state and to compare the outcome of the surgical procedures with the same period of 2018 and 2019. Methods: A retrospective analysis of the patient charts from patients submitted to surgery in the months of March and April of the year 2020 was conducted and compared to the same period on the previous two years. The primary endpoint was death at 30 days or during hospital stay and the secondary endpoints were pathology classification, grade of ischemia, amputation, amputation level, type of surgery (endovascular, conventional or hybrid), time of hospital stay and reintervention. Results: There were 98 patients submitted to surgery in the COVID period (CP), compared to 286 in the Non-COVID period (NCP). There was no significant difference in the age (70 years (17–98) in the CP vs. 69 (17–92) in the NCP, p=.13) or sex profile of the patients (76% male (n=74) in the CP vs. 70% (n=196) in the NCP, p=.26). There was no statistical difference in mortality (5% (n=5) in the CP vs. 5% (n=13) in the NCP, p=.88). There was a statistically significant decrease in conventional surgery (43% (n=42) in the CP vs. 57% (n=164) in the NCP, p=.04), but no statistically significant difference in length of hospital stay(10 (0–77) days in the CP vs. 7 (0–118) in the NCP, p=.6), and reintervention (18% (n=18) in the CP vs. 16% (n=45) in the NCP, p=.58). PAD corresponded to 75% (n=73) of the admissions in the CP vs. 48% (n=137) in the NCP, p=.02. CLTI corresponded to 99% (n=70) of the PAD population in the CP, vs. 93% (n=114) in the NCP, p=.1, with a significant increase in the number of patients presenting with Rutherford Grades 5 and 6 (81% (n=57) in the CP, vs. 68% (n=77) in the NCP, p=.03). There was a non-significant decrease in amputation rate (35% (n=25) vs. 40% (n=49), p=.49) and increase of major limb amputation (52% (n=13) vs. 39% (n=19), p=.27). The second most frequent pathology was aneurysmal aortic and iliac disease, but there was a statistically significant reduction in the number of patients treated (5% (n=5) in the CP vs. 13% (n=36) in the NCP, p=.05). All aortic aneurysms treated in 2020 were ruptured (100% (n=5) vs. 42% (n=15) in the NCP, p=0.2). There was no significant difference in mortality in urgent aortic aneurysm repair between groups (60% (n=3) in the CP vs. 47% (n=7) in the NCP, p=.77). Conclusions: COVID-19 restrictions manifested mainly in the type of pathology treated and the number of patients operated on. The gravity of the underlying pathology, manifested by more serious wounds and advanced CLTI at presentation, did not increase mortality nor was reflected on limb amputations rates. Aortic and iliac aneurismal disease was the second most common pathology treated but with a significant decrease in total number of cases and no significant difference in mortality.